The Importance of How Regions are Constructed - Nyqvist, Roger (Current Swedish Archaeology, 2002)
In this article the author discuss how many regions can be identified in the province of Bohuslän. Region is a construction that covers everything from landscape, people and economic structure, to nature, political structure and structures for subsistence. We have to keep this fact in mind, because these aspects, will be the reasons for how and why our material remains have the shape and distribution that they do. Different materials within the region can also be the result of the agricultural history, as well as the influences of the interested group of collectors could create for the artefacts. Therefore it seems most correct to use the term region only in the geographic sense.